2019
DOI: 10.3390/v11020187
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Chlorotic Spot Virus (TCSV) Putatively Incorporated a Genomic Segment of Groundnut Ringspot Virus (GRSV) Upon a Reassortment Event

Abstract: Tomato chlorotic spot virus (TCSV) and groundnut ringspot virus (GRSV) share several genetic and biological traits. Both of them belong to the genus Tospovirus (family Peribunyaviridae), which is composed by viruses with tripartite RNA genome that infect plants and are transmitted by thrips (order Thysanoptera). Previous studies have suggested several reassortment events between these two viruses, and some speculated that they may share one of their genomic segments. To better understand the intimate evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
(39 reference statements)
3
5
0
Order By: Relevance
“…It is worth mentioning that GRSV isolates grouped in two distinct clusters, one containing only GRSV isolates and another in which GRSV isolates intercalate with TCSV isolates. These observations confirm the recent proposal by Silva et al (2019) that TCSV represents the first reported interspecific reassortant orthotospovirus genome.…”
Section: Phylogenetic Analyses Based On the M Rna Segmentsupporting
confidence: 92%
See 4 more Smart Citations
“…It is worth mentioning that GRSV isolates grouped in two distinct clusters, one containing only GRSV isolates and another in which GRSV isolates intercalate with TCSV isolates. These observations confirm the recent proposal by Silva et al (2019) that TCSV represents the first reported interspecific reassortant orthotospovirus genome.…”
Section: Phylogenetic Analyses Based On the M Rna Segmentsupporting
confidence: 92%
“…New reassortant genomes were detected neither in Brazil nor in the Dominican Republic by analyzing the genome composition of the orthotospovirus isolates. However, based on the recent work performed by Silva et al (2019), the TCSV found in this study, most likely is a reassortant species.…”
Section: Phylogenetic Analyses Based On the M Rna Segmentsupporting
confidence: 49%
See 3 more Smart Citations